2011
DOI: 10.1038/leu.2011.199
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous knockdown of survivin improves chemotherapeutic response in ALL models

Abstract: Although the cure rate of newly diagnosed acute lymphoblastic leukemia (ALL) has improved over the past four decades, the outcome for patients who relapse remains poor. New therapies are needed for these patients. Our previous global gene expression analysis in a series of paired diagnosis-relapse pediatric patient samples revealed that the antiapoptotic gene survivin was consistently upregulated upon disease relapse. In this study, we demonstrate a link between survivin expression and drug resistance and test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
53
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 44 publications
(51 reference statements)
0
53
0
Order By: Relevance
“…We demonstrated that expression of both of these genes could be decreased after vorinostat exposure. Improving chemosensitivity by performing knock-down experiments of BIRC5 has been shown by us 26 and others 29 and has further supported its role in chemoresistance. Similarly, down-regulation of genes such as NR3C1 and BTG1 have been linked previously to glucocorticoid resistance, 30 and we observed herein increased expression of these genes after vorinostat treatment.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We demonstrated that expression of both of these genes could be decreased after vorinostat exposure. Improving chemosensitivity by performing knock-down experiments of BIRC5 has been shown by us 26 and others 29 and has further supported its role in chemoresistance. Similarly, down-regulation of genes such as NR3C1 and BTG1 have been linked previously to glucocorticoid resistance, 30 and we observed herein increased expression of these genes after vorinostat treatment.…”
Section: Discussionmentioning
confidence: 98%
“…Our results indicate that vorinostat reverses significantly the expression of genes that are differentially regulated at relapse, some of which are linked to tumor formation and progression, and, most importantly, may have a role in chemoresistance. Of particular interest are BIRC5 and FOXM1, which are associated with a wide range of cancers [25][26][27][28] and were up-regulated in our relapse signature. We demonstrated that expression of both of these genes could be decreased after vorinostat exposure.…”
mentioning
confidence: 99%
“…3,[14][15][16] BIRC5 is particularly interesting, as it is associated with a wide range of cancers and has been shown to be a marker of poor prognosis. We have demonstrated that down-regulation of BIRC5 in vitro leads to increased chemosensitivity, 17 and we have established a pediatric clinical trial targeting BIRC5 with a locked nucleic acid oligonucleotide for relapsed ALL (www.clinicaltrials.gov: #NCT01186328). In addition to confirming many of our previous findings, this current analysis has identified additional genes of interest, including up-regulation of FOXM1, an oncogenic transcription factor, which is expressed in all embryonic tissues and proliferating cells.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in combination with chemotherapy are ongoing. EZN-3042, the antisense oligonucleotide used in these in vivo experiments, is capable of inhibiting survivin expression and tumor growth in vivo (33) and improves chemotherapeutic response in vitro (46). EZN-3042 is currently in phase I clinical trials in human cancer.…”
Section: Discussionmentioning
confidence: 99%